Una nueva subespecie de Gentiana ovatiloba (Gentianaceae) - Villarreal Quintanilla, Jose Angel (Instituto de Ecología, A.C., 1997)
Gentiana ovatiloba Kusn. ssp. michoacana Villarreal is proposed as a new taxon from central Mexico. The population here described as a new subspecies is characterized by spreading, broadly foliaceous calyx lobes, broadly elliptic to ovate leaf blades and corolla lobes smaller than those of the typical subspecies. An illustration is presented.